(untitled) (Medicina y Seguridad del Trabajo, 2022)
Introduction: Common mental disorders (CMD), cause individual suffering and significate impairment to health, have a negative impact on the well-being of the individual, financial circumstances and society. Physicians’ response has been to grant disability in order to mitigate symptoms. But the dilemma involved in this response is that rest is beneficial only if it maintains a functional balance for the patient and return to work. Under this approach, it is stated that psychosocial interventions allow preparing the individual to return to work. Method: The design of this review is descriptive in scope and mixed in approach. The search was carried out from the following databases: PubMed/MEDLINE, ELSEVIER, SciELO, Academic Google. Temporality search criteria were articles published in the last 5 years, from December 06 to December 30, 2019. Results: 28 full-text articles were analyzed; the scientific evidence was supported in 13 controlled studies. We found a moderate evidence that the interventions applied improve symptoms and reduce the number of days of disability in patients with CMD. Evidence level B of GRADE. Conclusions: psycho-social interventions facilitate a healthy and sustainable return to work. However, for this to happen, they must address not only the individual with an inability to work, but also their interaction with their workplace.